A Study of Some New Hermite–Hadamard Inequalities via Specific Convex Functions with Applications - Moin-ud-Din Junjua; Ather Qayyum; Arslan Munir; Hüseyin Budak; Muhammad Mohsen Saleem; Siti Suzlin Supadi (Mathematics, 2024)
Convexity plays a crucial role in the development of fractional integral inequalities. Many fractional integral inequalities are derived based on convexity properties and techniques. These inequalities have several applications in different fields such as optimization, mathematical modeling and signal processing. The main goal of this article is to establish a novel and generalized identity for the Caputo–Fabrizio fractional operator. With the help of this specific developed identity, we derive new fractional integral inequalities via exponential convex functions. Furthermore, we give an application to some special means.